Millennials, Generation Z and the future of tourism - Corbisiero, Fabio (Channel View Publications, 2022)
"This book examines the lifestyles, expectations and plans of Millennials and Generation Z and how they are redefining tourism. It explores the present and future challenges faced by the tourism industry as a result of the generational turnover and the role a generational perspective can play in helping the industry recover from the COVID-19 crisis"--
Keywords: Geschichte 1981-2010; Jahrgang; Generation; Tourismus; Tourism / Social aspects; Hospitality industry / Social aspects; Leisure industry / Social aspects; Generation Y / Attitudes; Generation Z / Attitudes; Popular culture / Social aspects; Accueil (Tourisme) / Aspect social; Loisirs / Industrie / Aspect social; Génération Internet / Attitudes; Génération Z / Attitudes; Culture populaire / Aspect social